“The Migrated Others”: Mission as Practicing Compassionate Presence - Bangun, Maraike Joanna Belle (Transformation, 2021)
One of the popular missional consensuses in the context of migration is seeing migrants as “moving targets” for evangelism. There is an urge to respond differently realising that migrants are not merely workers for economic welfare but persons created in the image of God. To reconstruct a model of mission that is embedded in the complex reality of migration, this paper will look into the details of three narratives of Indonesian and Filipino migrants who live and attend a Charismatic church in Sabah, Malaysia. It will give insights into the process of othering and discover the quality of compassion in their lives. Based on their experiences, I argue mission as a compassionate presence provides a sound theological basis for churches to respond to the continuous othering of migrants. It invites us to rethink evangelism, not solely as winning souls for Christ, but to embody Christ by being present.